Total Synthesis of Homogeneous Variants of Hirudin P6: A Post‐Translationally Modified Anti‐Thrombotic Leech‐Derived Protein1. (11th March 2014) - Hsieh, Yves S. Y.; Wijeyewickrema, Lakshmi C.; Wilkinson, Brendan L.; Pike, Robert N.; Payne, Richard J.
Abstract Hirudin P6 is a leech‐derived anti‐thrombotic protein which possesses two post‐translational modifications, O‐glycosylation and tyrosine sulfation. In this study we report the ligation‐based synthesis of a library of hirudin P6 proteins possessing homogeneous glycosylation and sulfation modifications. The nature of the modifications incorporated was shown to have a drastic effect on inhibition against both the fibrinogenolytic and amidolytic activities of thrombin and thus highlights a potential means for attenuating the biological activity of the protein.